VILLAGE FINANCIAL MANAGEMENT PROBLEMS IN ACCOMPLISHING A GOOD GOVERNANCE IN SUBURBAN GOVERNMENT - Endang Sulistyaningsih (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This qualitative research study was conducted to explore and analyze the role of the village government in the preparation of the Village Revenue and Expenditure Budget (APBDes) in the perspective of Law No. 6/2014 on Villages. The results show that the existence of the mentioned law requires a preparatory process for Village Government in preparing Village Budget. For this reason, the role of the Regional Government is also needed and very important in realizing good governance in the village administration. The Regional Government should provide socialization and the Village Government need to invite the community to participate in preparing the APBDes village regulations in a measured, integrated and synergized manner to meet the needs of the Village community.